Targeted disruption of the insulin receptor gene in the mouse results in neonatal lethality. - Joshi, R L (1996)
Targeted disruption of the insulin receptor gene (Insr) in the mouse was achieved using the homologous recombination approach. Insr+/- mice were normal as shown by glucose tolerance tests. Normal Insr-/- pups were born at expected rates, indicating that Insr can be dispensable for intrauterine development, growth and metabolism. However, they rapidly developed diabetic ketoacidosis accompanied by a marked post-natal growth retardation (up to 30-40% of littermate size), skeletal muscle hypotrophy and fatty infiltration of the liver and they died within 7 days after birth. Total absence of the insulin receptor (IR), demonstrated in the homozygous mutant mice, also resulted in other metabolic disorders: plasma triglyceride level could increase 6-fold and hepatic glycogen content could be five times less as compared with normal littermates. The very pronounced hyperglycemia in Insr-/- mice could result in an increased plasma insulin level of up to approximately 300 microU/ml, as compared with approximately 25 microU/ml for normal littermates. However, this plasma level was still unexpectedly low when compared with human infants with leprechaunism, who lack IR but who could have extremely high insulinemia (up to > 4000 microU/ml). The pathogenesis resulting from a null mutation in Insr is discussed.